Pengembangan Media Laboratorium Virtual untuk Mendukung Pembelajaran Praktikum SMA - Anang Purwoko (Teknodika, 2019)
This research aims to: 1) develop a virtual laboratory media as a supporter of the implementation of high school physics practicum; and 2) know the effectiveness of the use of virtual laboratories in high school physics learning. This research uses research and development (R & D) methods. The procedure for developing virtual laboratory media is carried out through: 1) field studies, literature studies, about the implementation of practicum in physics learning, interviews with teachers, monitoring of school equipment to support the implementation of physics practicum. 2) development: pre-production, production, and post-production, and 3) At this stage what is done is to study the effectiveness of the virtual laboratory media that have been developed on the level of student understanding through performance. The developed virtual laboratory media obtained a score of feasibility by material experts, media experts and students of 4.1 with good categories suitable for use in the learning process. The results of this study indicate: 1) There are significant differences in the pre-test and post-test scores in the experimental class with the sig value. 0,000. 2) There is a significant difference in the value of the post-test in the experimental class and the control class with a significance value of 0.039. Based on the results of the effectiveness test, it can be concluded that the use of laboratory media in high school physics teaching and learning activities significantly increases learning outcomes that can be used to increase the use of direct equipment